Can evil create? Lévinas in conversation with tikkun olam and Kierkegaard - Westin, Anna (Nordisk judaistik, 2018)
In this article, I look at the phenomenological expression of creativity through language as a way of relating to the self and others. Employing the Jewish concepts of the yetzerim, or impulses, philosophically, I suggest that these instances of existential engagement further develop the ethical act of tikkun olam, or the mending of the relational world. Moving beyond theodicies of good and evil, I will develop this account of relation by drawing on Emmanuel Lévinas’s and Søren Kierkegaard’s philosophy of subjectivity. I argue, therefore, that language can express particular accounts of relationality that can serve to clarify the ambiguous relationship between good and evil.